Zmartwychwstanie Jezusa jako klucz do interpretacji dziejów świata (Ap 5,6-10) - Siemieniec, Tomasz (Verbum Vitae, 2009)
The article discusses the role of Christ the Lamb in the light of Rev 5,6-10. In the first plane Christ appears in the glory of his victory. A visible sign of this victory is the place in the midst of the divine throne. At first his victory consists in martyr’s death. It entitled God to enter into a new bond with the people purchased for him. But the victory of the Lamb cannot be limited only to the martyrdom. For he appears in this vision as "standing, as though it had been slain". Such pose suggests victory not only through the martyrdom, but also through the resurrection. The victory achieved by the Lamb gives him right to take the scroll: from the right band of "the One, who is sitting on the throne". This scroll symbolizes divine plan toward the world and the people. Banding of the scroll to the Lamb means to initiate this scheme. For this reason the resurrection of Christ the Lamb can be seen as a key event to the accomplishment of God’s purpose. Divine project is being realized in the history of the world and 1he people. Attitude of men expresses either approval of 1he divine plan or refusal of it. In this context we can speak about judgment (it is suggested by OT-background of 1he symbol of a scroll-book). Judgment consists in a division of humankind in to two groups. One group includes those people who are on God’s side. They accept divine plane (which culminates in the resurrection of Christ) and by their life participate in the fulfilment of it. The other group rejects divine project by coming out against God and Lamb. The sentence is simply a consequence of their choice: the reward for the faithful and punishment for the disloyal ones.